2019
DOI: 10.1101/577635
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constructing a Draft Map of the Cannabis Proteome

Abstract: Recently we have seen a relaxing on the historic restrictions on the use and subsequent research on the cannabis plants, generally classified as Cannabis sativa and Cannabis indica. What research has been performed to date has centered on chemical analysis of plant flower products, namely cannabinoids and various terpenes that directly contribute to phenotypic characteristics of the female flowers. In addition, we have seen many groups recently completing genetic profiles of various plants of commercial value.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
5
0
1
Order By: Relevance
“…The Cannabis (2n = 2x = 20) draft genome has a haploid genomic sequence of over 876Mb – 1000Mb (Laverty et al, 2019; McKernan et al, 2020) and transcriptome of at least 30,000 genes (van Bakel et al, 2011, Jenkins and Orsburn, 2019a,b,c). The genome displays large amount of polymorphism with a single nucleotide polymorphism (SNP) present every one in a hundred to one in fifty base pairs (McKernan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cannabis (2n = 2x = 20) draft genome has a haploid genomic sequence of over 876Mb – 1000Mb (Laverty et al, 2019; McKernan et al, 2020) and transcriptome of at least 30,000 genes (van Bakel et al, 2011, Jenkins and Orsburn, 2019a,b,c). The genome displays large amount of polymorphism with a single nucleotide polymorphism (SNP) present every one in a hundred to one in fifty base pairs (McKernan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Given the recent release of the 10 chromosome map of the cannabis genome (Grassa, 2018; Laverty et al, 2019), metabolomic and proteomic insight (Jenkins and Orsburn, 2019a,b) as well as a fully annotated version of the cannabis genome resulting from the completion of the NCBI Cannabis sativa Annotation Release 100 (Jenkins and Orsburn, 2019c), we set out to characterise the functional basis of the SNPs used in the study. The previously designed targets developed using Cansat 3 (von Bakel et al, 2011) were subjected to a BLASTn search (Altschul et al, 1990) constrained to the taxa Cannabis using the NCBI online interface (https://blast.ncbi.nlm.nih.gov) accessed October 31, 2019.…”
Section: Methodsmentioning
confidence: 99%
“…It has a diploid genome (2n=20) estimated to be 843 Mb for male plants and 818 Mb for female plants. Additionally, the species is believed to possess almost 30,000 genes (Jenkins and Orsburn, 2019b, 2019a; Henry et al, 2020; Hurgobin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It also provides comprehensive genetic information [22], as studies showed that differences between fiber-and drug-type cannabis are at a genome-wide level and not necessarily limited to genes involved in THC production [5]. The recent release of the 10-chromosome map of the cannabis genome [23][24][25][26][27] may improve the understanding of the genetic architecture, identify a superior set of SNPs associated with interesting traits, and reduce future targeted genotyping costs by using fewer but more accurate SNPs [28].…”
Section: Introductionmentioning
confidence: 99%